Insecticide Resistance and Mechanisms of Culex pipiens Populations in the Mediterranean and Aegean Regions of Turkey During 2017-2018 - Sare İlknur Yavaşoğlu; Fatih Mehmet Şimşek (Tehran University of Medical Sciences, 2022)
Background: Culex pipiens has a significant public health importance since it is an important vector of West Nile virus and Rift Valley fever virus. We, therefore, aimed to determine the insecticide resistance level in Cx. pipiens populations in the Aegean and Mediterranean regions of Turkey. Methods: Bioassays have been carried out against Dichlorodiphenyltrichloroethane (DDT) (4%), Malathion (5%), Fenitrothion (1%), Propoxur (0.1%), Bendiocarb (0.1%), Permethrin (0.75%) and Deltamethrin (0.05%). Biochemical analyses have been performed to detect non-specific esterase, mixed function oxidase, glutathione-s-transferase and acetylcholinesterase levels. A knockdown resistance (kdr) (L1014F) and Acetylcholinesterase (Ace-1) (G119S) mutations have been detected by using allele-specific primers and a polymerase chain reaction (PCR) amplification of specific alleles (PASA) diagnostic test was performed for detection of F290V mutation. Results: Bioassay results showed that all Cx. pipiens populations were resistant to DDT, Malathion, Fenitrothion, Bendiocarb, Propoxur and some of the populations have started to gain Permethrin and Deltamethrin resistance. Biochemical analyses results revealed that altered glutathione-s-transferases, P450 monooxygenases, esterase levels might be responsible for DDT, organophosphate, carbamate and pyrethroid resistance in Cx. pipiens populations. Results showed mild to high frequency of L1014F, low frequency of F290V but no Ace-1 G119S mutation within the populations. Additionally, acetylcholinesterase insensitivity was not significantly high within the most of these populations. Conclusion: Overall results may help to fulfil the lacking information in the literature regarding insecticide resistance status and underlying mechanism of Culex pipiens populations of the Mediterranean and Aegean region of Turkey by using all bioassays, molecular tests and biochemical assays.